A well-being framework for impact evaluation: The case of the UK offshore wind industry. (April 2017) - Hattam, Caroline; Hooper, Tara; Papathanasopoulou, Eleni
Abstract: Growing levels of energy consumption and concern over the environmental consequences of energy production are leading to an increased investment in renewable energy generation. Despite an important relationship between energy production, consumption and well-being, little attempt has been made to provide a holistic assessment of how renewable energy sectors can contribute to different aspects of human well-being. This paper develops an impact evaluation framework that can be used to capture societal-level impacts of change on primarily objective well-being and applies it to the case of the UK offshore wind industry. As such, the framework goes beyond the traditional view of economic, social and environmental impact assessment and evaluation capturing wider aspects of societal costs and benefits as well as sustainable development. The framework proves a useful tool for organising the available evidence and suggests a broadly positive impact of the UK offshore wind industry. While further testing and refinement of the framework is needed, it could be easily transferred for well-being assessment of other industries and interventions.